Dual specificity phosphatase 1 as a non-invasive circulating biomarker candidate in preeclampsia - Andrieu, Jonatane; Donet, Agathe; Cocallemen, Jean-François; Charbonnier, Guillaume; Resseguier, Noémie; Paganini, Julien; Mège, Jean-Louis; Mezouar, Soraya; Bretelle, Florence (Frontiers in Endocrinology, 2025)
IntroductionPreeclampsia (PE) is a multisystem pregnancy complication. Factors pointing to a placental origin are the development of the pathology only during pregnancy, and its disappearance in the post-partum period.MethodsHere, we aim to identify early predictive biomarkers. Whole blood and serum samples were collected at the time of the first event of PE (V1) and same samples after remote delivery (30-60 postpartum days, V2). These two samples enabled investigation of PE markers found in V1 but absent in V2. To confirm that these candidates are associated with PE, an investigation of associated placental biopsy was also realized (J0).ResultsOur study identified a specific signature of PE including five Gene Ontology clusters including “angiogenesis and differentiation”, “cell-cycle”, “cell-adhesion”, “inflammatory response” and “cellular metabolism”. DUSP1 (Dual Specificity Phosphatase 1) gene was found specifically modulated in PE. PE women have a higher concentration of DUSP1 in serum compared to healthy donors. Interesting, at a distance from childbirth (V2), DUSP1 finds a rate like control group showing its predictive interest as a promising predictive biomarker of PE.DiscussionThe investigation of DUSP1 in a prospective study with a larger cohort, including the severity aspect of the disease, is necessary to confirm its value as a predictive biomarker in PE.